2018
DOI: 10.1136/tobaccocontrol-2018-054593
|View full text |Cite
|
Sign up to set email alerts
|

Age of tobacco use initiation and association with current use and nicotine dependence among US middle and high school students, 2014–2016

Abstract: IntroductionTobacco use mostly begins in adolescence and young adulthood. Earlier age of initiation of cigarette smoking is associated with greater nicotine dependence and sustained tobacco use. However, data are limited on the age of initiation of non-cigarette tobacco products, and the association between using these products and nicotine dependence and progression to established use.MethodsCombined 2014–2016 National Youth Tobacco Survey data, a nationally representative cross-sectional survey of US student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
68
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 32 publications
8
68
4
Order By: Relevance
“…It is possible, for instance, that students first tried a product within the past 30 days or that they first tried a product several years ago. However, research from 2014–2016 suggests that most youth have tried tobacco products between the ages of 12–14 [32]. Given the age range of high school students in our study (typically between 13–18), it is likely that for many students, their first product tried was not in the past 30 days.…”
Section: Discussionmentioning
confidence: 97%
“…It is possible, for instance, that students first tried a product within the past 30 days or that they first tried a product several years ago. However, research from 2014–2016 suggests that most youth have tried tobacco products between the ages of 12–14 [32]. Given the age range of high school students in our study (typically between 13–18), it is likely that for many students, their first product tried was not in the past 30 days.…”
Section: Discussionmentioning
confidence: 97%
“…However, EC advertising surges in youth-oriented new media, and greatly extends its reach at low costs in recent years [ 11 , 12 , 27 ]. As tobacco use at young ages predicts regular use in adulthood and most established smokers initiate smoking in adolescence, [ 53 55 ] the online media become essential for recruiting young users of new tobacco products. More stringent regulations of tobacco advertising in online media are needed to curb adolescent use of new products.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent decline in semen quality and an increase in incidence of testicular cancer in western men over the past century has been linked to lifestyle factors [43, 44]. According to the National Youth Tobacco Survey data published in 2018, the median age for smoking initiation in USA was reported to be 12.6 years [45], that coincides with the onset of puberty. Several studies have reported the adverse effects of smoking [4649], alcohol abuse [42, 47, 49], and caffeine intake [49, 50] on semen quality and DNA integrity.…”
Section: Discussionmentioning
confidence: 99%